2011
DOI: 10.4028/www.scientific.net/amr.409.170
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterisation of New Superelastic and Low Elastic Modulus Ti-Nb-X Alloys for Biomedical Application

Abstract: Ti-Nb based alloys are well known to their good mechanical properties, shape memory effect, superelasticity, as well as good biocompatibility. The Ti-24Nb (at%) binary alloy presents a shape memory behavior and low elastic modulus. Our study is focused on the improvement of their mechanical properties by adding a third alloying element (oxygen, nitrogen or silicon). Addition of 0.5 at% of N or O modifies drastically the mechanical behavior of Ti-24Nb alloy that exhibits superelastic behavior instead of shape m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Therefore, Ti-Nb alloy can be one of the best candidates instead of Ti-Ni alloy because of their non-toxic elements. Also, binary Ti-Nb alloy has good mechanical properties, shape memory effect, superelasticity, as well as good biocompatibility at room temperature [22]. Besides, mechanical properties of Ti-Nb alloy can be further improved by adding the third elements into it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Ti-Nb alloy can be one of the best candidates instead of Ti-Ni alloy because of their non-toxic elements. Also, binary Ti-Nb alloy has good mechanical properties, shape memory effect, superelasticity, as well as good biocompatibility at room temperature [22]. Besides, mechanical properties of Ti-Nb alloy can be further improved by adding the third elements into it.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, mechanical properties of Ti-Nb alloy can be further improved by adding the third elements into it. Ramarolahy et al added N, O, and Si to Ti-Nb and they found that after adding 0.5 at% of N, O, and Si, the TiNb-based SMA showed good superelastic properties and low Young's moduli that make them good candidates for biomedical applications [22]. Al-Zain, et al showed that by adding Mo the maximum recovery and transformation strains of a Ti-Nb alloy increased [23].…”
Section: Introductionmentioning
confidence: 99%